Estimating changes in streamflow attributable to wildfire in multiple watersheds using a semi-distributed watershed model - Wells, Ryan, author; Niemann, Jeffrey D., advisor; Kampf, Stephanie, committee member; Nelson, Peter, committee member (Colorado State University. Libraries, 2023)
Over half of western U.S. water supply is sourced from forested lands that are increasingly under wildfire risk. Studies have begun to isolate the effects of wildfire on streamflow, but they have used coarse temporal resolutions that cannot account for the numerous, interconnected watershed processes that control the responses to rainfall events. To address these concerns, we developed a method to isolate fine-scale (daily) effects of fire from climate. Wildfire effects were represented by the difference between measured post-fire daily streamflow and simulated unburned post-fire daily streamflow from a hydrologic model calibrated to pre-fire conditions. The method was applied to track hydrologic recovery after wildfires in six burned watersheds across the western U.S.: North Eagle Creek, NM (2012 Little Bear Fire), Lopez Creek, CA (1985 Las Pilitas Fire), and City Creek, Devil Canyon Creek, East Twin Creek, and Plunge Creek, CA (2003 Old Fire). All six watersheds experienced prolonged increases of post-fire streamflow, with the most consistent changes occurring during periods of low streamflow. Following 6 years of increased streamflow, Lopez Creek experienced 6 years of reduced streamflow, before returning to pre-fire streamflow behavior 12 years after the fire. North Eagle Creek and the four watersheds affected by the Old Fire continued to demonstrate elevated streamflow 9 and 18 years post-fire, respectively. This study demonstrates the utility of examining post-fire streamflow at daily resolution over multiple years. In particular, these results captured the variability of change across flow frequencies during recovery periods that would not be quantifiable otherwise.